Spoof Surface Plasmon Polaritons Power Divider with large Isolation - Shiyan Zhou (Nature Portfolio, 2018)
Abstract Periodic corrugated metal structure is designed to support and propagate spoof surface plasmon polaritons (SSPPs) wave in the microwave frequencies. In this paper, firstly a plasmonic waveguide consisting of oval-ring shaped cells is proposed with the performance of high transmission efficiency in a wide frequency range. The coplanar waveguides (CPWs) with 50 Ω impedance are adopted to feed the energies or extract signals at both ends of the plasmonic waveguide. Then a well-isolated power divider is constructed based on the SSPPs waveguides aiming to equally split the energy of the SSPPs wave into two equal parts. The stepped-impedances are co-designed with the three input/output ports of the power divider to achieve the impedance-matching between the SSPPs waveguides and the coplanar waveguides. Besides, a single resistor is placed in the middle of two symmetrical half oval-rings to realize the isolation between the two output ports over the spectrum of 4.5–7.5 GHz. Finally, both plasmonic waveguide and the power divider are fabricated and tested to verify the predicted characteristics.